Isaiah 53:3: The «novissimum virorum»: a whole profile in just one verse = Jesaja 53,3: Das «novissimum virorum» : ein ganzes Profil in nur einem Vers - Schmid Pfändler, Brigitta (Vulgata in dialogue, 2023)
This study clarifies the question of the subject described in verse Isa 53:3. The linguistic analysis of the Latin verse of Jerome's Vulgata sacra is brought into dialogue with the other main ancient languages Hebrew and Greek. As a result of these investigations, linguistic phenomena can be established which provide further information for exegesis. Against this background two fundamental questions arise, about the topic of the verse and its implementation in the syntax and semantics of the verse. To this end, the verses in the three languages are contrasted and analysed in relation to the representation of the subject.